Assessment of medication adherence and quality of life among patients with type 2 diabetes mellitus in a tertiary hospital in Kelantan, Malaysia - Nazmi Liana Azmi; Nurul Aida Md Rosly; Hock Chun Tang; Anis Fariha Che Darof; Nor Dini Zuki (IIUM Press, International Islamic University Malaysia, 2021)
Introduction: Previous studies have reported the relationship between medication adherence and quality of life are interrelated. However, many of the results were found to be conflicting. This study aimed to assess the level and association of medication adherence and quality of life among type 2 diabetes mellitus patients in Raja Perempuan Zainab II Hospital, Kelantan, Malaysia. Materials and methods: A cross-sectional survey was conducted among adult type 2 diabetes mellitus patients on treatment for over 1 year using convenience sampling at outpatient.  Medication Compliance Questionnaire (MCQ) and revised Diabetes Quality of Life Questionnaire (DQOL) instrument were self-administered to eligible subjects. Data were analysed using GNU PSPP version 0.8.5 and reported for descriptive statistics as well as correlation of both parameters. Results: A total of 200 patients were recruited and they were mostly at the age of 40 to 60 years old. The mean (SD) score for MCQ was 26.0 (1.6) with the majority of them were non-adherent (55.0%, n=110). The mean (SD) score for overall revised DQOL instrument was 25.5 (8.9) while each domain of "satisfaction", "impact" and "worry" had mean (SD) scores of 12.0 (5.0), 7.7 (3.4) and 5.9 (2.7), respectively. The scores obtained were only approximately half of the possible range of scores for QoL. There was no significant correlation between total score of medication adherence and quality of life when tested using Pearson's correlation (r=-0.083, p=0.240). Independent t-test also demonstrated no significant relationship between medication adherence status and quality of life (p=0.883). Conclusion: Type 2 diabetes mellitus patients in our setting had unsatisfactory adherence but exhibited acceptable quality of life. We observed that both variables were not associated with one another. Further research is warranted to identify potential factors affecting non-adherence to medication.